Effects of deep tillage and crop rotation on soil biological properties in the Humid Pampas (Argentina) - Ferrari, Manuel Carlos; De Battista, Juan José; Ostojic, Juan Jose Ra (International Soil Tillage Research Organization, 2025)
Soil biological properties are considered early indicators of changes in soil quality induced by management practices. The objective of this study was to assess the impacts of deep tillage and crop rotation on selected soil biological properties in the 10th year of a long-term trial conducted under no-tillage. The experiment was initiated in 1997 at INTA-Pergamino Experimental Station (Argentina) on a Pergamino silty-loam (Typic Argiudoll). Three deep tillage treatments (main plots) and three rotations (subplots) were compared in a split-plot design with three replications. Deep tillage treatments included: paraplow at the beginning of the study only (A); paraplow at the beginning of the study and then periodically (B); and no paraplow (C). Crop sequences were: wheat/sorghum-maize (a); Oats+Vetch (cover crop)/soybean (b); and wheat/soybean-maize (c). Composite soil samples were collected in november 2007 at depths of 0-5 and 5-20 cm to determine microbial biomass C (MBC), microbial biomass N (MBN), respiration (RESP), metabolic quotient (qCO2), and potential of N mineralization measured by 7-day anaerobic incubations (PNM-AI). Deep tillage only affected MBN at 0-5 cm depth, the highest value being achieved by the C treatment. Crop rotation had significant effects on MBC, MBN, PNM-AI and RESP at 0-5 cm depth. Thus, the b sequence showed increases of 22, 43 and 29% for MBC, MBN and PNM-AI, respectively, whereas the c rotation resulted in a 24% decrease for RESP relative to the average of the other two treatments. Effects of tillage and rotation, and the interaction between them, were not significant for any variable at 5-20 cm depth. The positive impact of the b sequence on soil biological properties at the soil surface might be associated with both the longer period of time during the year the soil is occupied by living roots and the quality of the crop residues under this rotation.